School Counselors' Perceptions of Barriers to Implementing a RAMP-Designated School Counseling Program. Issue 1 (January 2019) - Hilts, Derron; Kratsa, Kristi; Joseph, Matthew; Kolbert, Jered B.; Crothers, Laura M.; Nice, Matthew L.
This study examined what school counselors perceive to be consistent barriers to implementing a program that adheres to the ASCA National Model. The Recognized ASCA Model Program (RAMP) designates such implementation. Principal component analysis revealed six common barriers: lack of confidence, lack of administrative support, time spent on clerical and office work, lack of teacher and parent support to implement aspects of the ASCA National Model, time spent on testing and monitoring, and time constraints. Logistic regression indicated three of the six barriers were significant predictors of RAMP status. We discuss implications for the school counseling profession.